Perubahan Kadar Saturasi Oksigen pada Pasien Dewasa yang Dilakukan Tindakan Suction Endotrakeal Tube di Ruang ICU RSUD Ulin Banjarmasin - Hammad Hammad; M. Ichwan Rijani; Marwansyah Marwansyah (Poltekkes Kemenkes Mataram, 2020)
Handling for airway obstruction due to excessive accumulation of secretions can be done with suction, suction is done by inserting suction catheter tube into endotracheal tube or tracheostomy which aims to liberate airway. Endotracheal suction in critically ill patients can cause increased intracranial pressure, brain swelling and systemic hypoxemia may even lead to death. The easiest way to find out hypoxemia is by looking at the patient's oxygen saturation of peripheral oxygen saturation is a presentation of hemoglobin binds with oxygen in the arteries with normal values between 95-100%.This research aims to analyze changes in oxygen saturation levels of patients before, during and after the suction endotracheal tube performed in Intensive Care Unit Ulin Banjarmasin Hospital. This research method is quantitative with comparative design. The population in this research are all patients who had endotracheal tube and suction was done, the sample in the research are 25 respondents with Probability sampling technique, analyzed by paired T test.The results of this research at the time of 1